Monitoring In-Situ Seismic Response on Rock Slopes Using Ambient Noise Interferometry: Application to the 2019 Changning (Mw 5.7) Earthquake, China - Huang, Huibao; Dai, Shigui; Xie, Fan (Frontiers in Earth Science, 2021)
Study the mechanical response of the rock slope to moderate earthquakes is important to understand the local rheology of the landslide and earthquake interactions, and to mitigate the risks associated with subsurface geological process in tectonically active mountains belt. To complement existing point measurements from surface observations (e.g., GPS, InSAR), ambient noise-based velocity change ($δ v/v$) allows for remote observations of mechanical state changes of the slope, at depth and continuously in time. We herein investigate the seismic responses of the Pubugou rock slope, a typical steep rock slope in south-west China, to the 2019 Mw 5.7 Changning earthquake. We apply ambient noise interferometry to the slope, and measure the coda wave velocity changes at frequency band between 2- to 20 Hz with a one hour temporal resolution, 2 days before and 14 days after the earthquake. We observe that the significant co-seismic wave velocity decreases caused by the Changning earthquake is up to ~0.9% followed by a gradual logarithm recovery process over 2 weeks. Earthquake-induced stress sensitivity of $δ v/v$ on the slope is estimated of $\sim3.2×10^{-8} Pa^{-1}$. By analysis the co-seismic and post-seismic $δ v/v$ with different time lapse of the coda, we not only characterize the healing process on the slope, but also constrain such changes to $\sim$70 m in depth. Our study highlights the possibility to quantitative characterize the slope weakness by using moderate earthquakes in mountainous areas in future.